6
$\begingroup$

Considering this integral and sum are equal, how can we show that and evaluate its closed form?

$$\int_{0}^{1}\ln{(-\ln{x})}\cdot{\mathrm dx\over 1+x^2}=-\sum_{n=0}^{\infty}{1\over 2n+1}\cdot{2\pi\over e^{\pi(2n+1)}+1}=I_S\tag1$$

Note:

$$\int_{0}^{1}{\mathrm dx\over 1+x^2}=\sum_{n=0}^{\infty}{(-1)^n\over 2n+1}\tag2$$ An attempt:

$u=-\ln{x}$ then $xdu=-dx$

$(1)$ becomes

$$\int_{0}^{\infty}\ln{u}\cdot{\mathrm du\over e^u+e^{-u}}={1\over 2}\int_{0}^{\infty}\ln{u}\cdot{\mathrm du\over \cosh{u}}\tag3$$

$(3)$, seem complicate.

$\endgroup$
  • $\begingroup$ Relevant: math.stackexchange.com/questions/121545/… $\endgroup$ – nospoon Feb 26 '17 at 8:07
  • $\begingroup$ @nospoon: In my answer I have mapped the series value given in this question with the value of integral in the question you linked. $\endgroup$ – Paramanand Singh Feb 26 '17 at 9:07
  • 2
    $\begingroup$ We also have $$I_S=-\pi \sum_{k=1}^\infty (-1)^k \ln \left( \tanh \frac{\pi k}{2} \right)$$ $\endgroup$ – Yuriy S Feb 26 '17 at 12:33
4
+150
$\begingroup$

The following is based on theory of theta functions and elliptic integrals. Let $0 < q < 1$ and consider the function $$a(q) = \sum_{n = 1}^{\infty}\frac{q^{n}}{n(1 + q^{n})}\tag{1}$$ and $$b(q) = \sum_{n \text{ odd}}^{\infty}\frac{q^{n}}{n(1 + q^{n})}\tag{2}$$ We can see that $$b(q) = a(q) - \frac{a(q^{2})}{2}\tag{3}$$ Now we have \begin{align} a(q) &= \sum_{n = 1}^{\infty}\frac{1}{n}\sum_{m = 1}^{\infty}(-1)^{m - 1}q^{mn}\notag\\ &= \sum_{m = 1}^{\infty}(-1)^{m - 1}\sum_{n = 1}^{\infty}\frac{q^{mn}}{n}\notag\\ &= \sum_{m = 1}^{\infty}(-1)^{m}\log(1 - q^{m})\notag\\ &= \log\prod_{n = 1}^{\infty}\frac{1 - q^{2n}}{1 - q^{2n - 1}}\notag\\ &= \log\prod_{n = 1}^{\infty}\frac{1 - q^{n}}{(1 - q^{2n - 1})^{2}}\notag \end{align} Therefore \begin{align} 2b(q) &= 2a(q) - a(q^{2})\notag\\ &= \log\prod_{n = 1}^{\infty}\frac{(1 - q^{n})^{2}}{(1 - q^{2n - 1})^{4}}\cdot\frac{(1 - q^{4n - 2})^{2}}{(1 - q^{2n})}\notag\\ &= \log\prod_{n = 1}^{\infty}\frac{(1 - q^{2n})^{2}}{(1 - q^{2n - 1})^{2}}\cdot\frac{(1 - q^{4n - 2})^{2}}{(1 - q^{2n})}\notag\\ &= \log\prod_{n = 1}^{\infty}(1 - q^{2n})(1 + q^{2n - 1})^{2}\notag\\ &= \log\vartheta_{3}(q)\notag \end{align} and thus $$b(q) = \frac{1}{4}\log\frac{2K}{\pi}\tag{4}$$ where $K$ is complete elliptic integral for modulus $k$ corresponding to nome $q = e^{-\pi K'/K}$.

The value of integral as claimed here is $$-2\pi b(e^{-\pi})$$ This corresponds to $q = e^{-\pi}, k = 1/\sqrt{2}, K = \Gamma^{2}(1/4)/4\sqrt{\pi}$ and hence the integral in question is claimed to be $$-\frac{\pi}{2}\log\frac{1}{\pi}\frac{\Gamma^{2}(1/4)}{2\sqrt{\pi}} = \frac{\pi}{2}\log \left(\sqrt{2\pi} \Gamma\left(\frac{3}{4}\right) / \Gamma\left(\frac{1}{4}\right)\right)$$ and this is evaluated in the question linked by "nospoon" in his comment.

It is however desirable to have a direct proof that the integral is equal to the infinite series in question without making use of the answers of the linked question.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.